Outcomes of Arthroscopic vs Open Broström Surgery for Chronic Lateral Ankle Instability: A Systematic Review and Meta-Analysis of Comparative Studies. Issue 1 (January 2022) - Attia, Ahmed K.; Taha, Tarek A.; Khamis, Karim Mahmoud; Hunt, Kenneth J.; Labib, Sameh A.; Dhooghe, Pieter
Category: Ankle; Arthroscopy; Sports Introduction/Purpose: Ankle sprains are the most common ankle injury accounting for up to 85% of all ankle injuries, and nearly 20% of acute ankle sprains progress to chronic lateral ankle instability that requires surgical intervention. In recent years, there has been a growing interest in arthroscopic Broström techniques as an alternative to open surgery. In the past two years alone, four comparative studies have been published. Recent case series and cohort studies showed reliable improvement in clinical and radiographic outcomes with arthroscopic surgeryAIM. The current study aims at providing the foot and ankle surgery community with the most updated evidence comparing outcomes of open to arthroscopic Broström procedure for chronic lateral ankle instability. Methods: This article was performed following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Two independent authors searched several databases for relevant comparative studies in English literature were identified between database inceptions to May 2020. The primary outcomes were (1) Functional scores (KAFS, AOFAS) and (2) Pain score on VAS, whereas the secondary outcomes were differences in (1) anterior drawer and talar tilt, (2) surgical time and complications rate, (3) time to return to sports and weight-bearing. Population: Chronic lateral ankle instability (LAI)Intervention: Arthroscopic Broström procedure Control: Open Broström procedure Outcomes: Primary: Functional scores, pain Secondary: Anterior drawer and talar tilt, complications, time to return to sport and weight-bearing Results: A total of 408 patients in eight studies met the inclusion criteria were subjected to analysis. 193 (47.3%) patients underwent open surgery, while 215 (52.7%) patients underwent arthroscopic surgery. The one year-AOFAS was 80.05 vs. 88.6 in open and arthroscopic surgery, respectively (MD= -11.96, CI= -21.26, -2.76, I2= 82%, p= 0.01). The mean one year VAS was 2.05 and 1.45 in open and arthroscopic repair, respectively (MD= 0.31, CI= 0.09 to 0.54, I2=0%, p<0.001).The mean time to weight- bearing was 14.25 weeks and 9.0 weeks in open and arthroscopic repair, respectively (MD=1.89, CI= 1.24 to 2.54, I2=99%, p<0.001).There were no statistically significant differences in the time to RTP, postoperative anterior drawer, postoperative talar tilt, and operative time. The total complications rate in open and arthroscopic repair was 21.3% vs. 10%, with statistical insignificance (OR= 0.73, 95%CI= 0.39 to 1.38, I2=0%, p= 0.34). Conclusion: While technically more demanding, arthroscopic Broström is superior to open Broström-Gould surgery in AOFAS functional scores at six and twelve months, time to return to weight-bearing, and VAS pain scores. Operative time, complications rate, talar tilt, and anterior drawer tests are excellent and statistically comparable. Long-term clinical trials are required before recommending arthroscopic Broström as the new gold standard.